Strategic Orientation and Social Enterprise Performance. (June 2014) - Liu, Gordon; Takeda, Sachiko; Ko, Wai-Wai
Even though previous research indicates that an organization's pursuit of strategic orientation (SO) has positive effects on its performance, we have deepened and expanded our understanding of how this concept can also be applied to social enterprises (SEs). Using data collected from British and Japanese social enterprises, we examined the mediating roles of market effectiveness and consumer satisfaction in both the social and commercial domains with regard to SO effects on performance, as well as how performance in one aspect of practice positively moderates the impact of SO behavior in another. The results contribute to the development of a theory for understanding the concept of SO associated with social enterprise performance. More generally, this article contributes to the ongoing efforts to understand the strategic management aspect of social enterprises.